AWAPer: An R package for area weighted catchment daily meteorological data anywhere within Australia. Issue 5 (1st December 2019) - Peterson, Tim J.; Wasko, Conrad; Saft, Margarita; Peel, Murray C.
Abstract: Meteorological time‐series data are a fundamental input to hydrological investigations. But sourcing data is often laborious and plagued with difficulties. In an effort to improve efficiency and rigor we present an R‐package, named AWAPer (https://github.com/peterson-tim-j/AWAPer ), for the efficient estimation of daily area weighted catchment average and spatial variance of meteorological variables, including evapotranspiration. The package allows creation and updating of a data‐cube of gridded daily data from 1900 onwards. Once created, point and area weighted estimates can be extracted at user‐defined locations and time periods for anywhere within Australia. Examples of point and catchment average extraction are presented.